1994
DOI: 10.1007/bf00058973
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the repair tissue in articular cartilage defects using silver-enhanced colloidal gold immunostaining

Abstract: The newly developed silver-enhanced colloidal gold staining method was used in a rabbit model to characterize the repair tissue in large articular cartilage defects filled with a heterocyclic methacrylate polymer. By 6 weeks the resurfacing tissue consisted of highly organized hyaline-like articular cartilage, fully integrated with the adjacent normal cartilage. Immuno-histochemistry detected collagen type II, keratan sulphate, chondroitin 4-sulphate and chondroitin 6-sulphate in the matrix of the neocartilage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…PEMA/THFMA was previously shown to have excellent biological properties in the oral mucosa [S] as well as following intra-articular implantation [5]. In this study, synovial samples were also studied and confirmed that the polymer is biocompatible.…”
Section: Discussionsupporting
confidence: 73%
“…PEMA/THFMA was previously shown to have excellent biological properties in the oral mucosa [S] as well as following intra-articular implantation [5]. In this study, synovial samples were also studied and confirmed that the polymer is biocompatible.…”
Section: Discussionsupporting
confidence: 73%
“…Residual benzoyl peroxide initiator, still present in the PEMA, reacts with a tertiary amine ( N,N -dimethyl- p -toluidine), resulting in the formation of free radicals, capable of initiating polymerization of the THFMA monomer (Bhusate & Braden 1985; Riggs et al 2000). Thus far PEMA/THFMA has been investigated for potential uses in dental applications, ion, protein and drug release (Pearson et al 1986; Di Silvio et al 1994; Patel et al 1998, 2001b; Riggs et al 1999b, 2000; Di Silvio et al 2002) and also in the repair of bone and cartilage (Patel & Braden 1991a-c; Downes et al 1994; Reissis et al 1994a,b).…”
Section: Tetrahydrofurfuryl Methacrylate Scaffoldsmentioning
confidence: 99%
“…5a). Initially, the activity increased rapidly (day 2-6) and a plateau was reached (day [6][7][8][9][10][11][12][13][14]. Chondrocytes seeded on the unfoamed polymer showed higher metabolic activity than the foams but less than the Thermanox.…”
Section: Cell Metabolic Activitymentioning
confidence: 99%
“…Although non-biodegradable, the advantage of using this material is that it has been demonstrated to support the repair of fullthickness defects in vivo. Rabbits with osteochondral defects had the material implanted just below the level of the subchondral bone and after 8 months the defect had completely filled with dense cartilaginous tissue that was integrated into the surrounding normal cartilage [9][10][11]. In vitro studies, also using the non-porous PEMA/ THFMA, have demonstrated that the material supported bovine chondrocyte growth and differentiation [8,12,13].…”
Section: Introductionmentioning
confidence: 99%